21st Century Skills and School Culture as Predictors of Teaching Performance among Secondary School Techers of Region XI: A Convergent Design - MONTEBON, LEAH MARY; DAYAGANON, AVEE JOY (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This mixed methods study determined the status of 21st century skills and school culture as predictors of teaching performance among secondary school teachers in Region XI using a convergent design. Quantitative findings revealed that public secondary school teachers in Region XI, Philippines, exhibited a very high level of 21st century skills, indicating consistent use of modern teaching methods and essential competencies for effective instruction. The status of school culture was also rated as very high, signifying a positive, supportive, and nurturing environment conducive to both teaching and learning. Teaching performance was similarly rated as very high, reflecting teachers’ proficiency in delivering quality instruction, strong professional commitment, and positive student outcomes. Furthermore, the data showed minimal variability in teachers’ performance, suggesting a well-organized and supportive educational system. Qualitative findings provided deeper insights into these results. Teachers were found to be dedicated to fostering positive classroom interactions, creating innovative learning opportunities, and addressing the diverse needs of their students. However, challenges were also noted, particularly in managing the emotional and logistical complexities of modern classrooms. From the participants’ lived experiences, six essential themes emerged: using assessment data to guide students, designing innovative learning opportunities, demonstrating high regard for the profession, fostering positive classroom interactions, supporting the 21st century skills of students, and prioritizing meaningful relationships. The integration of both quantitative and qualitative data provided a comprehensive perspective on teaching performance. The findings revealed that 21st century skills and school culture significantly influenced teaching performance. These results underscore the belief that outstanding teaching performance is achieved through the merging and converging of 21st century competencies and a strong, supportive school culture.